IDENTIFYING PROSPECTIVE GOLD MINERALIZATION AREAS IN WESTERN KALBA (EASTERN KAZAKHSTAN): AN INNOVATIVE APPROACH - Diachkov, B.; Chernenko, Z.; Mizernaya, M.; Teut, E.V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
A new type of gold deposits In Eastern Kazakhstan is gold ores commonly found in hydrothermally altered carbonate rocks. We have suggested a geological-genetic model of their origin based on a volumetric stereo-metallogenic analysis of West Kalba and Zharma-Saur zones. Use has been made of comprehensive geologic-geophysical methods and high-precision analyses to develop criteria for predicting, prospecting and evaluating gold-carbonate formations, as well as identifying new prospective areas having category P2 and P3 gold resources. In addition to describing the geological structure of the Earth’s surface, this model applies to exploring its deeper strata, hence the term "volumetric or stereo metallogeny". Our research into the genesis of gold deposits in Western Kalba has yielded more accurate data on the geotectonic position of the gold-bearing structures and the age of gold mineralization, there being a connection between typical gold associations and particular ore parent formations. The local gold mineralization zones (West Kalba, Zhana-Boko-Zaisan), whose position is obliquely counter relative to the traditional north-westerly direction of the Altai structures, intersect the volcanic-sedimentary and terrigenous strata of different age (from Devonian to C2–3). These goldbearing zones are cut and metamorphosed by the Kalba-Narym Pluton granitoids, which points to their Pre-Permian age. The results of the laboratory tests performed on modern equipment in the laboratories IRGETAS D.Serikbaev EKSTU, analytical centers of IGM SB RAS (Novosibirsk, Russia) and the Natural History Museum in the UK (London) showed that gold-sulfide ores (primary and oxidized) contain free gold in the form of fine particles in pyrite and arsenopyrite. The nanoscale gold particle sizes range from microns to 0,1–0,5 mm. The gold particles are bright yellow in color and high purity (an average of 935 ‰). According to the X-ray diffraction analysis, the gold-bearing jasperoids are composed mainly of silica and iron oxides. The results of the atomic absorption analysis of rocks showed that gold has a very uneven distribution (from 0,1 to 33,5 g/t), while the silver content is low (from 0,06 to 2,66 g/t). Electron microscopy yielded new data on the distribution of noble metals (Au, Ag, Pt, Pd), associated chalcophiles and rare earth elements in the ores and host rocks, as well as mineral indicators for identifying new ore deposits.